2001
DOI: 10.1002/dvdy.1128
|View full text |Cite
|
Sign up to set email alerts
|

An SNF2 factor involved in mammalian development and cellular proliferation

Abstract: Members of the SNF2 (Sucrose Non-Fermenter) family of chromatin-remodeling proteins function in processes ranging from DNA repair to transcription to methylation. Using differential display, we recently identified a novel member of the SNF2 family that is highly expressed at the mRNA level in proliferating cells and is down-regulated during apoptosis. We have named this gene PASG (Proliferation-Associated SNF2-like Gene). Northern blot analysis of adult mouse tissues shows PASG to be highly expressed in prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…The hemimethylated DNA would be converted to fully methylated DNA, and the associated HDAC2 may then deacetylate newly deposited histones and allow for maintenance of a heterochromatic state once the DNA replication machinery has passed (Rountree et al, 2000). The strict correlation between Lsh expression and cell proliferation lends support for this idea (Raabe et al, 2001). This model is highly feasible for methylation in the context of DNA replication (maintenance methylation), however evidence from other cellular processes, particularly related to de novo methylation and methylation remodeling events occurring during embryogenesis, indicates that there may be additional mechanisms.…”
Section: Lshmentioning
confidence: 99%
See 1 more Smart Citation
“…The hemimethylated DNA would be converted to fully methylated DNA, and the associated HDAC2 may then deacetylate newly deposited histones and allow for maintenance of a heterochromatic state once the DNA replication machinery has passed (Rountree et al, 2000). The strict correlation between Lsh expression and cell proliferation lends support for this idea (Raabe et al, 2001). This model is highly feasible for methylation in the context of DNA replication (maintenance methylation), however evidence from other cellular processes, particularly related to de novo methylation and methylation remodeling events occurring during embryogenesis, indicates that there may be additional mechanisms.…”
Section: Lshmentioning
confidence: 99%
“…Since then, its expression has been found to be less restricted, however Lsh expression appears to be tightly correlated with cell proliferation (Geiman and Muegge, 2000;Raabe et al, 2001). Lsh knockout mice were generated and developed relatively normally.…”
Section: Lshmentioning
confidence: 99%
“…Given the homology of DDM1 and Lsh with chromatin-remodeling ATPases of the SNF2 family, it has been suggested that chromatin remodeling by DDM1 and Lsh may facilitate the processivity of DNMT enzymes on nucleosomal DNA templates (20,28). In agreement with the requirement for SNF2-like proteins to support DNA methylation in vivo, several studies have demonstrated that in vitro DNMT enzymes methylate DNA assembled into chromatin 10-to 20-fold less efficiently than naked DNA (11,25,31).…”
mentioning
confidence: 94%
“…Previous work showed that Lsh, also known as Proliferation-Associated SNF2-like Gene (PASG), is expressed ubiquitously in fetal mouse tissues and is linked with cell proliferation (Raabe et al 2001), as well as being essential in postnatal murine development (Geiman and Muegge 2000;Geiman et al 2001). Lsh −/− mice die within a few hours after birth with reduced body weight and a pathology suggesting that renal failure may be the direct cause of mortality.…”
Section: Is Chromatin Remodeling Necessary For Dna Methylation In Vivo?mentioning
confidence: 99%
“…This may have been indicative of the proliferating nature of lymphoid cells rather than tissue specificity, as expression is nearly ubiquitous in the developing mouse embryo Raabe et al 2001). Therefore, Lsh may be a proliferation factor like its highly homologous human counterpart PASG, which is associated with dividing cells.…”
Section: Is Lsh Involved In Remodeling Heterochromatin?mentioning
confidence: 99%